ANALISIS PEMANFAATAN DIGITAL MARKETING SEBAGAI MEDIA PEMASARAN PRODUK (STUDI PADA USAHA KULINER YANG BERMITRA DENGAN APLIKASI JASA TRANSPORTASI ONLINE DI KOTA KENDARI) - Kansa Dwi Rahmadania; Haji Saediman; Samsul Alam Fyka (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2024)
This study aims to analyze the extent to which digital marketing is utilized and its correlation with business characteristics and actors in the culinary industry that partner with online transportation service providers in Kendari City. The study population consists of 220 culinary businesses that partner with the Grab online transportation service application in Kendari City. The sample was selected using a simple random sampling technique. The sample size of 42 was determined using the Slovin formula with an error rate of 15%. The study employed a quantitative approach, and data analysis was conducted using descriptive analysis, Chi Square test, and contingency correlation test. The study revealed that only 30 culinary businesses in Kendari City, which partnered with online transportation service applications, utilized digital marketing as a marketing medium. Among them, only 12 businesses had a high level of utilization. The Chi Square analysis results indicate a weak relationship between the level of utilization of digital marketing and turnover characteristics of business. Business characteristics and business actors were found to have a relationship with the level of utilization of digital marketing.